Exercise Prevents Diet-Induced Cellular Senescence in Adipose Tissue - Schafer, Marissa J; White, Thomas A; Evans, Glenda; Tonne, Jason M; Verzosa, Grace C; Stout, Michael B; Mazula, Daniel L; Palmer, Allyson K; Baker, Darren J; Jensen, Michael D; Torbenson, Michael S; Miller, Jordan D; et al. (Diabetes (New York, N.Y.), 2016)
Considerable evidence implicates cellular senescence in the biology of aging and chronic disease. Diet and exercise are determinants of healthy aging; however, the extent to which they affect the behavior and accretion of senescent cells within distinct tissues is not clear. Here we tested the hypothesis that exercise prevents premature senescent cell accumulation and systemic metabolic dysfunction induced by a fast-food diet (FFD). Using transgenic mice that express EGFP in response to activation of the senescence-associated p16(INK4a) promoter, we demonstrate that FFD consumption causes deleterious changes in body weight and composition as well as in measures of physical, cardiac, and metabolic health. The harmful effects of the FFD were associated with dramatic increases in several markers of senescence, including p16, EGFP, senescence-associated β-galactosidase, and the senescence-associated secretory phenotype (SASP) specifically in visceral adipose tissue. We show that exercise prevents the accumulation of senescent cells and the expression of the SASP while nullifying the damaging effects of the FFD on parameters of health. We also demonstrate that exercise initiated after long-term FFD feeding reduces senescent phenotype markers in visceral adipose tissue while attenuating physical impairments, suggesting that exercise may provide restorative benefit by mitigating accrued senescent burden. These findings highlight a novel mechanism by which exercise mediates its beneficial effects and reinforces the effect of modifiable lifestyle choices on health span.